Analisis Upaya Penegakan Hukum Terhadap Krisis Lingkungan Atas Implikasi Pencemaran Udara Akibat Asap Kendaraan Bermotor di Daerah Khusus Jakarta (DKJ) Tahun 2023 - Mayzura Kamila Sukma; Febyola Alistya Senoaji; Kezia Ananda Restu (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
With the physical development of cities and industrial areas, as well as the development of transportation facilities, air quality also experiences changes in the composition of the atmosphere compared to normal conditions, which is characterized by the entry of polluting materials. Gasses and small particles/aerosols enter the air in constant quantities over long periods of time and affect not only human life but also animal and plant life. Currently, the development of electric vehicles in urban areas such as Indonesia and the Special Capital Region (DKJ) of course causes problems in the transportation system, also causes damage to common land by various interests and disrupts the existing air quality and also affects the atmosphere when pollution occurs. Transportation is the largest contributor to air pollution, namely around 85%, because transportation is a proven source of emissions. Therefore, law enforcement efforts to improve the transportation sector without ignoring other sectors, including strategic actions, must be prioritized. The number of buses and trains has also increased. It will also control the number of private cars and improve much of the public transportation system.